A simple modified surgical technique combined with tissue adhesive for steatocystoma multiplex. (10th May 2020) - Jiang, Long; Yan, Jianna; Chen, Xiaogang; Chen, Yuchong; Tang, Yichen
Abstract: Background: Steatocystoma multiplex (SM) is a disorder of the pilosebaceous unit characterized by multiple sebum‐containing dermal cysts. Psychological distress of patients is always derived from these undesirable lesions. Although various treatments have been attempted to improve cosmetic outcomes, no optimal treatment strategy has been established to date.. Aims: To provide a facile and practical surgical technique combined with tissue adhesive for the treatment of steatocystoma multiplex. Method: Forty patients diagnosed as SM were treated with simple modified surgical technique. After local anesthesia, the surface skin was incised about 1‐2 mm using a No. 11 blade. When the wall was punctured, the cyst should be squeezed to cause the contents to come out first. Then, we used single toothed forceps which were inserted through the narrow incision. When the cyst was exposed, the mosquito forceps grasp the portion of the cyst and pull it out gently. Then, the incisions were pressed locally, and tissue adhesive was employed to align them when there was no bleeding. We just took approximately 1‐2 minutes to excise one cyst completely. Result: We successfully treated forty SM patients with our simple modified surgical technique. After treatment, excellent clinical outcomes and minimal adverse effects were observed in this study. And more importantly, no recurrence was found 12 months after the surgery. Conclusion: Our simple modified surgical technique was proved to be practical and have excellent results in the long run. We highly recommend this treatment technique as the first‐line therapy for SM.